Calculation by iterative method of linear viscoelastic plate under biaxial tension; IOP Conference Series: Materials Science and Engineering; Vol. 177 : Mechanical Engineering, Automation and Control Systems (MEACS 2016) - Svetashkov A. A. Aleksandr Andreevich; Micinski J.; Manabaev K. K. Kairat Kamitovich; Vakurov A. A. (Numerical simulation of applied problems, 2017)
Title screen